A challenging diagnosis of a mucocele in the maxillary gingiva: Case report and literature review - Elsayed, Nagwan (Int J Surg Case Rep, 2021)
INTRODUCTION: Mucoceles are mucous extravasation phenomena resulting from spontaneous ductal rupture or, less commonly, a traumatic cutting of a salivary excretory duct. Occasionally, the appearance of a mucocele closely resembles a neoplastic lesion, and it can be difficult to diagnose. PRESENTATION OF CASE: A 74-year-old Japanese male patient was referred to our clinic with painless swelling related to the upper right canine-premolar area. Preoperative imaging of the lesion revealed that it was fluid-filled and the histopathological biopsy suggested a myxoid tumor. We excised the lesion with the patient under general anesthesia, using safety margins based on the histology of the biopsy specimen to reach the definitive diagnosis and treatment. The final pathological diagnosis was a mucocele in the vicinity with an aberrant small salivary gland. Follow-up visits showed complete healing of the epithelium, and no recurrence has been observed during the subsequent 30 months. DISCUSSION: In cases with a difficult definitive diagnosis based on medical history, diagnostic imaging and pathological examination, it is important to proceed carefully with the possibility of a tumor in mind. CONCLUSION: This case emphasizes that some mucous cysts are challenging for clinicians in terms of diagnosis and treatment due to an uncommon presentation.